1992
DOI: 10.1161/01.atv.12.4.430
|View full text |Cite
|
Sign up to set email alerts
|

Clopidogrel inhibits the binding of ADP analogues to the receptor mediating inhibition of platelet adenylate cyclase.

Abstract: Clopidogrel, like the homologous thienopyridine derivative tidopidine, selectively inhibits platelet aggregation induced by ADP. We have previously described two nucleotide-binding sites on platelets related to ADPmediated platelet responses. The first is a high-affinity binding she for 2-methylthio-ADP (2-MeSADP) that is linked to the inhibition of stimulated adenylate cyclase. The second is the 100-kd exofacial membrane protein aggregin, which is labeled by the reactive ADP analogue 5'-p-fluorosulfonyibenzoy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
115
0
2

Year Published

1996
1996
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 194 publications
(123 citation statements)
references
References 19 publications
(19 reference statements)
6
115
0
2
Order By: Relevance
“…10,11,17,33,34 The present study underscores the selectivity of clopidogrel for abolishing ADP-mediated platelet activation and its lack of significant inhibitory effects on TRAP-induced platelet activation ( Table 1). The inhibition of collagen-induced platelet aggregation by clopidogrel is explained by the contribution made by ADP secretion from platelets activated by collagen ( Table 1).…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…10,11,17,33,34 The present study underscores the selectivity of clopidogrel for abolishing ADP-mediated platelet activation and its lack of significant inhibitory effects on TRAP-induced platelet activation ( Table 1). The inhibition of collagen-induced platelet aggregation by clopidogrel is explained by the contribution made by ADP secretion from platelets activated by collagen ( Table 1).…”
Section: Discussionmentioning
confidence: 54%
“…22 Clopidogrel acts by irreversibly inactivating platelet ADP receptor-initiated signaling in a dose-dependent manner. 10,20,21 In a recently reported large-scale, randomized, controlled clinical trial, clopidogrel was shown to be significantly more effective than and at least as safe as aspirin in decreasing arterial thromboocclusive episodes in patients with symptomatic atherosclerotic disease. 22 Clinical trials reporting that ticlopidine plus aspirin markedly reduces thrombotic occlusion of coronary stents suggest that adding aspirin to clopidogrel therapy may enhance its antithrombotic efficacy.…”
mentioning
confidence: 99%
“…The thienopyridine compounds are prodrugs which have to be metabolized by the liver in order to generate active metabolites. The active metabolite of clopidogrel [107] covalently binds cysteine residues of the P2Y 12 receptor, thus precluding the binding of ADP [108][109][110]. Moreover, it has been recently reported that clopidogrel's active metabolite disrupts homopolymers of the P2Y 12 receptor expressed in lipid rafts and partitions them out of lipid rafts [111], pointing to the importance of oligomerization and membrane localization on the function of this receptor.…”
Section: The Platelet P2 Receptors As Molecular Targets For Antithrommentioning
confidence: 99%
“…Although CYP2C19 is not primarily involved in the metabolism of APs, it is an important enzyme involved in the metabolism of antidepressants and the antiplatelet drug, clopidogrel (16,25,26). Given that it is included in various commercially available genetic test kits, its genetic architecture is briefly discussed.…”
Section: Cyp2c19mentioning
confidence: 99%